Investigation of Nitrogenous and Algal Oxygen Demand Effect on Quality Evaluation of Effluent from Aerated Lagoons - Hassan khorsandi; Rahimeh Alizadeh; hooriye toosinejad; hadi poorghafar (آب و فاضلاب, 2014)
In this descriptive study, samples of the effluent from the maturation pond following the Miandoab aerated lagoons were measured in accordance with Standard Methods. The measurements were done with and without filtration in the presence and absence of nitrification inhibitor. The results were analyzed using repeated measures analysis of variance by SPSS version 16. The analysis of variance indicated significant differences in the annual mean five-day biochemical and chemical oxygen demand within paired groups (P